"Who Is David and Who Is – the Son of Jesse?". The Interpretation of the Figure of King David in the Development of Old Testament Theology - Viktor Komarnytskyy (The Biblical Annals)
The article addresses the issue of the numerous inconsistencies and contradictions found in the David cycle in 1 Sam 14 – 1 Kings 2. Usually, exegetes tend to believe that the biography of the king, especially the section the ‘History of David’s rise to power’, shows traces of two legends of different origins, regardless of whether the figure actually existed in Israel’s history. However, after comparing the inconsistencies in the portrayal of the king, it can be concluded that the basis of the legends about David may have been a real historical figure of a certain warrior whose biography can be traced from 1 Sam 27 – a certain warrior from the Philistine city of Ziklag who conquered the heights of Hebron and may be considered the founder of the Judah statehood.